2019
DOI: 10.5336/cardiosci.2019-70586
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care Agency and Associated Factors in Heart Transplant Patients

Abstract: Heart transplant patients must maintain their self-care at the highest level and take responsibility for their own treatment and care. The study determined the self-care agency of heart transplant patients and associated factors. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : This is a descriptive and cross-sectional study. The study universe consisted of 117 patients over the age of 18 who underwent heart transplant surgery at a university hospital. The study sample included 50 patients. The rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The high score obtained from the scale indicates the high level of self-care or self-care agency and power of the individual. There are a limited number of studies that determine the self-care ability in transplant patients (Çeliktürk & Durmaz Edeer, 2019; Li et al, 2020; Zhan et al, 2015). Similarly, a study on patients with cirrhosis found the mean score of self-care agency as moderate (Kepenek, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The high score obtained from the scale indicates the high level of self-care or self-care agency and power of the individual. There are a limited number of studies that determine the self-care ability in transplant patients (Çeliktürk & Durmaz Edeer, 2019; Li et al, 2020; Zhan et al, 2015). Similarly, a study on patients with cirrhosis found the mean score of self-care agency as moderate (Kepenek, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no significant difference between self-care and caregiving in our study. A study conducted by Ç eliktü rk in 2016 that involved patients with heart transplants has found that the status of patients receiving help did not affect their self-care behavior [30].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study on patients who received a LT, the anxiety was evaluated by State-Trait Anxiety Scale (STAI; Form I and II), depression was evaluated using the Beck Depression Scale (BDS), and the self-care was evaluated using the Self-Care Agency Scale (SCAS). All these scoring systems and scales were individually used in previous studies involving solid organ transplantation[ 17 - 19 ]. However, we have not encountered any study involving all three scales used together to evaluate a population of recipients.…”
Section: Introductionmentioning
confidence: 99%